CT features in amyloidosis of the respiratory system - comprehensive analysis in a tertiary referral center cohort - Brandelik, Simone Christine; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Röcken, Christoph; Huber, Laura; Basset, Marco; Kimmich, Christoph; Schönland, Stefan; Hegenbart, Ute; Nattenmüller, Johanna (European journal of radiology, 2020)
Purpose - Amyloidosis of the respiratory system is rare and challenging since imaging findings have several more prevalent alternative diagnoses. We analyze and quantify chest CT findings in a large tertiary referral center patient cohort with confirmed amyloidosis of the respiratory system. - Methods - 67 patients with histology-proven amyloidosis of the respiratory system and with available chest CT scans were retrospectively enrolled (years 2002-2018): 41 patients with local pulmonary parenchymal, 20 with local tracheobronchial, and 6 with systemic amyloidosis. CT was scored for findings like mass lesions, nodules, cysts, lymphadenopathy, calcifications and pleural, interstitial and tracheobronchial manifestations. Clinical data and imaging findings’ frequencies among patients with local pulmonary parenchymal and tracheobronchial amyloidosis were compared. - Results - Patients with local pulmonary parenchymal amyloidosis were older (67 vs. 56 years; P=0.013) and less frequently symptomatic for cough (24% vs. 70%; P=0.018) and bronchopulmonal infections (7% vs. 55%; P<0.001) than patients with tracheobronchial amyloidosis. Local pulmonary parenchymal amyloidosis showed higher frequency of mass-like lesions (41% vs. 0%; P=0.002) and nodules (95% vs. 20%; P<0.001, with 10 or more nodules in 56% vs. 0%; P<0.001 and predominantly pleura-associated in 32% vs. 0%; P=0.02). Tracheobronchial amyloidosis leads to wall thickening of the bronchi (100% vs. 5%; P<0.001) and the trachea (70% vs. 2%; P<0.001). Systemic amyloidosis went along with a predominant alveolar septal pattern in 4 out of 6 patients. - Conclusion - Patients with local pulmonary parenchymal amyloidosis differ significantly from patients with tracheobronchial amyloidosis regarding clinical data and CT findings’ frequencies. Being familiar with radiological manifestations of all three respiratory amyloidosis distribution patterns is essential to accelerate the diagnosis.